Odpowiedzi

2010-01-13T08:33:45+01:00
A )
4y - x = 6
17 y = 0
4y=6+x /:4
y=1,5+1/4x
17*(1,5+1/4x)=0
25,5+4,25x=0
4,25x=-25,5 /:4,25
x=-6
4y-(-6)=6
4y+6=6
4y=6-6
4y=0 /:4
y=0

b )
u = 4v
5u -v = 10
5*4v-v=10
20v-v=10
19v=10 /19
v=10/19
u=4*10/19
u=40/19
u=2 2/19

c )

x+ 3y =3
x-y=5
x=3-3y
3-3y-y=5
3-2y=5
-2y=5-3
-2y=2 /:-2
y=-1
x=3-3*(-1)
x=3-(-3)
x=3+3
x=6

d )

2x - y = 10
x+5y = -17
x=-17-5y
2*(-17-5y)-y=10
-34-10y-y=10
-11y=10+34
-11y=44 /:-11
y=-4
x=-17-5*-4
x=-17-(-20)
x=-17+20
x=3
1 4 1
Najlepsza Odpowiedź!
2010-01-13T08:43:16+01:00
A )
4y - x = 6
17 y = 0

4y - x = 6
y = 0

-x=6
y=0


x=-6
y=0


b )
u = 4v
5u -v = 10

5*4v-v=10
20v-v=10
19v=10
v=10/19

u=4*10/19
u=40/19

c )

x+ 3y =3
x-y=5

x=3-3y
3-3y-y=5
3-4y=5
-4y=5-3
-4y=2
y=-1/2

x=3-3*(-1/2)
x=3+3/2
x=4i1/2


d )

2x - y = 10
x+5y = -17

-y=10-2x
y=2x-10

x+5*(2x-10)=-17
x+10x-50=-17
11x=-17+50
11x=33
x=3

y=2*3-10
y=6-10
y=-4
1 5 1